2019
DOI: 10.1002/jctb.6233
|View full text |Cite
|
Sign up to set email alerts
|

Bioaugmentation of p‐chloronitrobenzene in bioelectrochemical systems with Pseudomonas fluorescens

Abstract: BACKGROUND: p-Chloronitrobenzene (p-CNB) is easily accumulated in the environment and subsequently is a threat to humans and the ecosystem. The anaerobic process as an important pathway for p-CNB degradation has a relatively low degradation rate. This study illustrated that the strain Pseudomonas fluorescens was evaluated as the biocatalyst for bioaugmentation to enhance the p-CNB removal in bioelectrochemical system (BES). RESULTS:When the initial p-CNB concentration was 100 mg L −1 , the p-CNB removal effici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…At 500 mA g −1 , the initial specific capacities are 569.50 mA h g −1 , and the capacity retention is 87.35% after 500 cycles. Wang et al 140 successfully synthesized TiO 2 nanoparticles encapsulated in graphene composites (GTO) by a simple hydrothermal method. The initial specific capacity is up to 652.8 mA h g −1 at 0.1 A g −1 , and reaches 198 mA h g −1 at 1 A g −1 after 300 cycles.…”
Section: Graphenementioning
confidence: 99%
See 1 more Smart Citation
“…At 500 mA g −1 , the initial specific capacities are 569.50 mA h g −1 , and the capacity retention is 87.35% after 500 cycles. Wang et al 140 successfully synthesized TiO 2 nanoparticles encapsulated in graphene composites (GTO) by a simple hydrothermal method. The initial specific capacity is up to 652.8 mA h g −1 at 0.1 A g −1 , and reaches 198 mA h g −1 at 1 A g −1 after 300 cycles.…”
Section: Graphenementioning
confidence: 99%
“…139 (b) Long-term cycle performance of GTO at 1 A g −1 for 300 cycles. 140 (c) 3D structure of NiO@graphene. 141 (d) Preparation of GF.…”
Section: Dalton Transactions Reviewmentioning
confidence: 99%
“…102 Rhodococcus also contribute to the degradation of aromatic compounds in MFCs, specically chlorophenols. 74,103 Song et al 104 demonstrated that p-chloronitrobenzene (p-CNB) can be removed by MFC using Pseudomonas uorescens.…”
Section: Biocatalysts For Organic Carbon Pollutants Removal In Mfcsmentioning
confidence: 99%
“…Varied physical, chemical, and biological technologies have been explored to treat NCB in water ( Le et al, 2011 ; Li and Zhu, 2014 ; Huang et al, 2016 ; Liu et al, 2016 ; Chen et al, 2018 ; Song et al, 2020 ). Among which advanced oxidation technology (AOT) is more reliable due to its high degradation efficacy and lower secondary pollution.…”
Section: Introductionmentioning
confidence: 99%